THE USE OF COOPERATIVE INTEGRATAED READING AND COMPOSITION METHOD IN LEARNING TO WRITE PROCEDURAL TEXTS IN CLASS XI OF SMK PUI GEGESIK IN THE 2022/2023 ACADEMIC YEAR - Sondari, Sondari; Fajri, Khoirul; Subaweh, Ahmad Maskur (Transpublika Publisher, 2023)
This study aims to investigate the use of the Cooperative Integrated Reading and Composition (CIRC) method on the learning outcomes of procedural text writing among 11th-grade students in Multimedia 3 at SMK PUI Gegesik for the academic year 2022/2023. The hypothesis, in this case, H0 is rejected, and Ha is accepted. Therefore, it demonstrates the effectiveness of teaching procedural text writing using the CIRC method among the students at SMK PUI Gegesik for the academic year 2022/2023. The study employed an experimental approach with a pretest-posttest control group design. Data collection included tests and observations of both teachers and students during the procedural text writing lessons, which were utilized to determine the effectiveness and engagement of the CIRC method. Based on observational data, it was evident that students were more active and their procedural text writing skills improved compared to their previous performance when using the CIRC method. The analyzed test results showed that the average learning outcomes for the control group were 66.8, while for the experimental group using the CIRC method, it was 82.6. The t-value was 6.044, and the t-table value was 1.677. Consequently, the t-value (6.044) exceeded the t-table value (1.677), leading to the rejection of H0 and acceptance of Ha. This indicates the effectiveness of teaching procedural text writing to 11th-grade students in Multimedia 3 using the CIRC method at SMK PUI Gegesik for the academic year 2022/2023.